Bagaço de cana-de-açúcar e raízes de alface empregados como biossorventes de íons metálicos em meio aquoso - Milani, Priscila Aparecida (Universidade Federal de São Carlos, 2017)
Sugarcane bagasse and hydroponic lettuce roots were used as biosorbents for Cu(II), Fe(II), Zn(II) and Mn(II) removal from mono and multielement solutions, as well as in lake water, at pH 5.5, in batch processes. These biomasses were studied in natura (lettuce roots, NLR, and sugarcane bagasse, NSB) and chemically modified with HNO3 (lettuce roots, MLR, and sugarcane bagasse, MSB). The results showed that higher adsorption efficiency was achieved with the modified biomass, with the exception of lettuce roots, which also presented similar efficiency when used in natura. The removal experimental quantities (qexp) in monoelement solution, calculated using the Langmuir isothermal model for Cu(II), Fe(II), Zn(II) and Mn(II) were respectively, 1.22, 1.08, 1.40 and 1.23 mg g-1 in NLR, and 1.69, 1.68, 1.09 and 1.48 mg g-1 in MLR and 0.58, 0.036, 0.40 e 0.24 mg g-1 in NSB, and 1.30, 1.41, 1.55 and 1.02 mg g-1 in MSB. The removal experimental quantities (qexp) in multielement solution containing Cu(II), Fe(II), Zn(II), and Mn(II) in multielement solution were 1.28, 1.41, 1.29 and 1.05 mg g-1 in NLR, and 1.30, 1.09, 1.72 e 1.64 mg g-1 in MLR, and 0.47, 0.58, 0.09 and 0.02 mg g-1 in NSB, and 1.30, 1.09, 1.06 and 1.62 mg g-1 in MSB, respectively. We used the isothermal models of Langmuir and Freundlich, however for multielement solutions the adsorption did not conform to the Freundlich isotherm. In the kinetic studies with modified biomasses, sorption was achieved in the first 5 minutes and reached equilibrium in 30 min. The O-H, C-O-C, C-C, C-H, and C=O groups were found in the characterization of the biomass sorption sites by Fourier transform infrared spectrometry (FTIR). In the determination of the biomass surface charges using blue methylene and red amaranth dyes, there was a predominance of negative charges. Modified biomasses were used in the adsorption of Cu(II), Fe(II), Zn(II), and Mn(II) in lake water, in which retention of 24.31, 14.50, 8.21, and 8.03 mg g-1 by MLR, and 13.15, 10.50, 5.14 and 6,10 mg g-1 by MSB was found, respectively.
Sugarcane bagasse and lettuce roots used as biosorbent of metallic ions in aqueous medium
Keywords: Biossorção; Biomassa; Biorremediação; Descontaminação de águas; Biosorption; Biomass; Bioremediation; Water decontamination; CIENCIAS AGRARIAS::AGRONOMIA